2023
DOI: 10.1590/1984-3143-ar2022-0051
|View full text |Cite
|
Sign up to set email alerts
|

Group-training of rams at puberty for artificial vagina-mediated semen collection and its influence on semen quality and sexual behavior

Abstract: There is a paucity of information with respect to group-training for artificial vagina and its influence on semen characteristics and sexual behavior of young untrained rams. A total of 18 healthy Najdi rams (with an initial body weight of 40-45 Kg and 7-8 month-old) were consequently used herein to test the usefulness of group-training for artificial vagina-mediated semen collection during the breeding season. Rams were randomly segregated into three groups ( n = 6 rams per protocol), a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 26 publications
0
0
0
Order By: Relevance
“…Through vast amounts of information presented by different studies involving the analysis of male reproductive hormones, it has been confirmed that the sexual activity of rams is under the control of androgenic hormones that act at the level of the hypothalamus (preoptic area) (see complete reviews of Orihuela-Trujillo, 2012). One of the main hormones released by rams is testosterone, which influences sexual and metabolic activity and varies throughout the year; it is present at low concentrations outside the reproductive season, while testosterone levels increase above the threshold required for the ram to show sufficient sexual behaviour to detect a female in oestrus ( Bahadi et al, 2023 ) and induce her to cover and become pregnant within the same season. Ungerfeld (2021a) systematically characterises sexual behaviour and describes the main scenarios that can influence sexual development from lambing to adulthood.…”
Section: Sexual Behaviour Of Ramsmentioning
confidence: 99%
See 1 more Smart Citation
“…Through vast amounts of information presented by different studies involving the analysis of male reproductive hormones, it has been confirmed that the sexual activity of rams is under the control of androgenic hormones that act at the level of the hypothalamus (preoptic area) (see complete reviews of Orihuela-Trujillo, 2012). One of the main hormones released by rams is testosterone, which influences sexual and metabolic activity and varies throughout the year; it is present at low concentrations outside the reproductive season, while testosterone levels increase above the threshold required for the ram to show sufficient sexual behaviour to detect a female in oestrus ( Bahadi et al, 2023 ) and induce her to cover and become pregnant within the same season. Ungerfeld (2021a) systematically characterises sexual behaviour and describes the main scenarios that can influence sexual development from lambing to adulthood.…”
Section: Sexual Behaviour Of Ramsmentioning
confidence: 99%
“…The aim of this review is not to describe all of the factors involved in or influencing sexual behaviour and the male effect, as comprehensive reviews have been previously undertaken over the years (see full reviews by Pretorius, 1972 ; Tilbrook and Cameron, 1990 ; Rosa and Bryant, 2002 ; Ungerfeld et al, 2004 ; Perkins and Roselli, 2007 ; Orihuela-Trujillo, 2012; Roselli, 2020 ; Ungerfeld, 2021a , b ). However, it is necessary to mention that consistent studies have been carried out over the years investigating factors that influence sexual behaviour (see Figure 2 ), where the different factors that can influence both wool and hair rams have been shown ( Bahadi et al, 2023 ). It is important to bear in mind that there are differences which, in one way or another, affect the mating of a ram to an oestrus ewe to a greater or lesser extent, as well as the achievement of optimal gestation of two offspring.…”
Section: Sexual Behaviour Of Ramsmentioning
confidence: 99%